Association between CD24 Ala/Val polymorphism and multiple sclerosis risk: A meta analysis. Issue 15 (April 2020) - Yang, Wan; Zhou, Wang; Zhang, Bo-Kang; Kong, Ling-Suo; Zhu, Xing-Xing; Wang, Rui-Xiang; Yang, Yue; Chen, Yun-Fei; Chen, Lan-Ren
Abstract: Background: The aim of this study was to explore the association between CD24 Ala/Val polymorphism and susceptibility of multiple sclerosis (MS). Methods: A comprehensive literature search for relevant studies was performed on google scholar, PubMed, Web of science, Embase, the Chinese National Knowledge Infrastructure and the Chinese Biology Medicine. This meta-analysis was conducted using the STATA 11.0 software and the pooled odds ratio with 95% confidence interval was calculated. Results: Seven case-control studies were included in this meta-analysis. The results showed significant association between CD24 Ala/Val polymorphism and susceptibility to MS. Stratified analysis by areas also showed significant association in Asians. However, no association was found in Europeans. Conclusion: This study suggested that the CD24 Val allele was associated with an increased risk of MS and larger-scale studies of populations are needed to explore the role of CD24 Ala/Val polymorphism during the pathogenesis of MS.